Innovative hydrocarbon sensor for real drive emission testing: optimization of the gas inlet - Nurain, Rozy; Norazlianie, Sazali; Saiful Anwar, Che Ghani; Maurice, Kettner (Akademia Baru, 2021)
Hydrocarbon emission is very bad for human health. Many efforts were made to reduce the pollution of hydrocarbon sensor especially in vehicle. For that, the development of hydrocarbon sensor for emission testing on the road is one of the great approaches to compare the results from laboratory test and in real driving test. This work focused on numerical investigation and optimization of hydrocarbon sensor prototype that is using glow plug as the heat source. Heat is important in facilitating ionization process for ion current measurement. Therefore, numerical optimization of inlet design and simulation using AVL Fire was done and reported in the following work to obtain the maximized performance of hydrocarbon sensor. We found that the optimum conditions for heating gas inside the chamber is when the inlet create a swirl flow and at low velocity.